Emerging Role of PARP Inhibitors in Metastatic Triple Negative Breast Cancer. Current Scenario and Future Perspectives - Barchiesi, Giacomo; Roberto, Michela; Verrico, Monica; Vici, Patrizia; Tomao, Silverio; Tomao, Federica (Frontiers in Oncology, 2021)
Triple negative tumors represent 15% of breast cancer and are characterized by the lack of estrogen receptors, progesterone receptor and HER2 amplification or overexpression. Approximately 25% of patients diagnosed with triple negative breast cancer carry a germline BRCA1 or 2 mutations. They have an aggressive biology and chemotherapy has been the mainstay of treatment for a long time. Despite intensive therapies, prognosis is still poor, and many patients will eventually relapse or die for cancer. Therefore, novel targeted agents that can increase treatment options for this disease are urgently needed. Recently, a new class of molecules has emerged as a standard of care for patients with triple negative breast cancer and germline BRCA1 or 2 mutation: poly (ADP-ribose) (PARP) inhibitors. In the first part of the review, we summarize and discuss evidence supporting the use of PARP inhibitors. Currently, two PARP inhibitors have been approved for triple negative metastatic breast cancer: Olaparib and Talazoparib, based on two-phase III trial which showed a progression free survival benefit when compared to chemotherapy. Safety profile was manageable with supportive therapies and dose reductions/interruptions. Also, other PARP inhibitors are currently under investigation such as Talazoparib, Rucaparib and Veliparib. Subsequently, we will discuss the potential role of PARP inhibitors in the next future. Clinical research areas are investigating PARP inhibitors in combination with other agents and are including patients without germline BRCA mutations: ongoing phase II/III studies are combining PARP inhibitors with immunotherapy while phase I and II trials are combining PARP inhibitors with other targeted agents such as ATM and PIK3CA inhibitors. Moreover, several clinical trials are enrolling patients with somatic BRCA mutation or patients carrying mutations in other genes than BRCA1/2 involved in homologous recombination repair pathway (e.g. CHECK2, PALB2, RAD51 etc).